Integrating Insults: Using Fault Tree Analysis to Guide Schizophrenia Research across Levels of Analysis - MacDonald III, Angus W.; Zick, Jennifer L.; Chafee, Matthew V.; Netoff, Theoden I. (Frontiers in Human Neuroscience, 2016)
The grand challenges of schizophrenia research are linking the causes of the disorder to its symptoms and finding ways to overcome those symptoms. We argue that the field will be unable to address these challenges within psychiatry’s standard neo-Kraepelinian (DSM) perspective. At the same time the current corrective, based in molecular genetics and cognitive neuroscience, is also likely to flounder due to its neglect for psychiatry’s syndromal structure. We suggest adopting a new approach long used in reliability engineering, which also serves as a synthesis of these approaches. This approach, known as fault tree analysis, can be combined with extant neuroscientific data collection and computational modeling efforts to uncover the causal structures underlying the cognitive and affective failures in people with schizophrenia as well as other complex psychiatric phenomena. By making explicit how causes combine from basic faults to downstream failures, this approach makes affordances for 1) causes that are neither necessary nor sufficient in and of themselves, 2) within-diagnosis heterogeneity, and 3) between diagnosis co-morbidity.